Physiological Tradeoffs of Immune Response Differs by Infection Type in Pieris napi - Keehnen, Naomi L. P.; Kučerová, Lucie; Nylin, Sören; Theopold, Ulrich; Wheat, Christopher W. (Frontiers in Physiology, 2021)
Understanding the tradeoffs that result from successful infection responses is central to understanding how life histories evolve. Gaining such insights however can be challenging, as they may be pathogen specific and confounded with experimental design. Here, we investigated whether infection from gram positive or negative bacteria results in different physiological tradeoffs, and whether these infections impact life history later in life (post-diapause development), in the butterfly Pieris napi. During the first 24 hours after infection (3, 6, 12, 24 hours), after removing effects due to injection, larvae infected with Micrococcus luteus showed a strong suppression of all non-immunity related processes while several types of immune responses were upregulated. In contrast, this tradeoff between homeostasis and immune response was much less pronounced in E. coli infections. These differences were also visible long after infection, via weight loss and slower development, as well as an increased mortality at higher infection levels during later stages of development. Individuals infected with M. luteus, compared to E. coli, had a higher mortality rate, and a lower pupal weight, developmental rate and adult weight. Further, males exhibited a more negative impact of infection than females. Thus, immune responses come at a cost even when the initial infection has been overcome, and these costs are likely to affect later life history parameters with fitness consequences.